A new type of weak open sets via idealization in bitopological spaces - D. J., Sharma; Kilicman, Adem; L. N., Mishra (Universiti Putra Malaysia, 2021)
The main objective of this article is to define and study a kind of weak open sets called weakly bI-open sets with respect to an ideal in bitopological spaces. Additionally, we introduce some basic features of this notion.